INDICATIONS OF UNFAIR BUSINESS COMPETITION IN DETERMINING AIRCRAFT RATES ASSOCIATED WITH LAW NUMBER 5 OF 1999 CONCERNING MONOPOLY AND UNFAIR BUSINESS COMPETITION (CASE STUDY OF KPPU KANWIL IV SURABAYA) - Syaiful, Muhammad; Waluyo (JARES (Journal of Academic Research and Sciences), 2024)
This study intends to find out the legal norms for the behavior of airlines in setting very low prices for scheduled domestic commercial airline tickets with the aim of eliminating competitors in the same class and the same route based on the perspective of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition , and describes the obstacles experienced by the Commission for the Supervision of Business Competition (KPPU) which has the authority to supervise and investigate this case. This study uses the Juridical Empirical Research method and concludes that by eliminating the rules regarding the requirements for adding flight frequencies that can be carried out by airlines on one route, it creates gaps for airlines with a larger fleet advantage to be able to carry out selling and loss practices, namely by setting fares lower than its competitors but with a greater number of flying frequencies causing a decrease in the competitiveness of these routes, this is clearly not in accordance with the rule of reason for the issuance of the Law on Anti-Monopolistic Practices which aims to increase competition in the market and pay attention to the balance between business actors and the constraints experienced by KPPU as the competent authority in this case is that there are no rules regarding the option of forced summons that can be carried out by the KPPU in order to present the reported party in the framework of investigating a case which results in a delay in completing the case